Impact of the new hazard classes in the CLP regulation on EU chemicals legislation - Diana Kättström; Anna Beronius; Urban Boije af Gennäs; Christina Rudén; Marlene Ågerstrand (Environmental Sciences Europe)
Abstract The EU recently introduced four new hazard classes to the Classification, Labelling and Packaging Regulation (CLP) (EC) 1272/2008. The classes are endocrine disruption for human health (ED HH) and the environment (ED ENV), persistent, bioaccumulative and toxic (PBT) or very persistent and very bioaccumulative (vPvB), and persistent, mobile and toxic (PMT) or very persistent and very mobile (vPvM). This action was a direct consequence of the EU’s Chemicals Strategy for Sustainability, which aims at strengthening the protection of human health and the environment, as well as reinforcing the CLP Regulation as the central piece of the chemicals legislation. This study examined the regulatory obligations triggered by these new hazard classes, as well as the existing obligations for endocrine disrupters and PBT/vPvB substances identified in other EU regulations. In addition, we compared the CLP criteria for endocrine disruption and PBT/vPvB to criteria existing in other EU regulations and investigated how these criteria are used in the EU chemicals legislation. We found that the implementation of the new hazard classes under the CLP into existing EU chemicals legislation will require the revision of all regulations that rely on the CLP hazard criteria for risk management. Without revision, the immediate impact of the new hazard classes will only extend to six regulations and the regulatory obligations they contain, all of which apply to substances classified under any of the CLP hazard classes. Meanwhile, substances with endocrine disrupting and PBT/vPvB properties are already being identified and regulated using criteria from regulations other than the CLP. When comparing the criteria for identification of endocrine disrupters and PBT/vPvB substances across the chemicals legislation, we found that the criteria differed between regulations. The findings aim to support the efficient implementation of the new CLP hazard classes and harmonization of criteria across regulations, in line with the Chemicals Strategy for Sustainability.